Economic and environmental review of Waste-to-Energy systems for municipal solid waste management in medium and small municipalities. (September 2017) - Fernández-González, J.M.; Grindlay, A.L.; Serrano-Bernardo, F.; Rodríguez-Rojas, M.I.; Zamorano, M.
Highlights: Proposed methodology selects the optimal solution for energy valorisation of MSW. Economic, environmental and territorial factors for WtE have been analysed. Energy valorization is economically viable in medium-low production areas. WtE generate territorial and environmental benefits in MSW management. Abstract: The application of Directive 2008/98/CE on Municipal Solid Waste (MSW) implies the need to introduce technologies to generate energy from waste. Incineration, the most widely used method, is difficult to implement in low populated areas because it requires a large amount of waste to be viable (100, 000 tons per year). This paper analyses the economic and environmental costs of different MSW-to-Energy technologies (WtE) in an area comprising of 13 municipalities in southern Spain. We analyse anaerobic digestion (Biomethanization), the production of solid recovered fuel (SRF) and gasification, and compare these approaches to the present Biological Mechanical Treatment (BMT) with elimination of the reject in landfill, and incineration with energy recovery. From an economic standpoint the implementation of WtE systems reduces the cost of running present BMT systems and incineration; gasification presents the lowest value. From the environmental standpoint, Life Cycle Assessment shows that any WtE alternatives, including incineration, present important advantages for the environment when compared to BMT. Finally, in order to select the best alternative, a multi-criteria method is applied, showing that anaerobic digestion is the optimal solution for the area studied.